Konsep Dasar Kurikulum Pai - Aulia, Fairus; Wanto, Deri; Idris, Muhammad; Kristina, Epa (Publikasi Indonesia, 2025)
Islamic Religious Education (PAI) has a strategic position in the national education system because it plays a role in shaping the character and spirituality of students. The curriculum as an important tool in education must be designed systematically and sustainably in order to be able to answer the challenges of the times. This study aims to examine the basic concepts of the PAI curriculum, including the definition, roles and functions, components, and position of the curriculum in education. The method used is a literature study of relevant references. The results of the study show that the PAI curriculum not only functions as a tool for transmitting Islamic values, but also as an instrument for developing students' potential in the spiritual, intellectual, and social dimensions. The PAI curriculum not only functions as a tool for transmitting Islamic values, but also as an instrument for developing students' potential in spiritual, intellectual, and social dimensions. This curriculum has a structure consisting of interrelated objectives, materials, strategies, and evaluation components and forms a complete education system. The PAI curriculum also acts as a bridge between the noble values of Islam and the context of students' lives that continue to develop, so innovation and adaptation are needed in its design so that it remains relevant and applicable in the modern era.